Climate-Smart Integrated Pests and Diseases Management for Smallholders in Ghana - Obeng Adomaa, Faustina (2025)
This infographic presents strategic partnership among agri-small and medium scale enterprises and public-sector actors supported by technical assistance from AICCRA through the International Institute of Tropical Agriculture (IITA) leading to the development and deployment of bundled solution for climate-smart integrated pest and diseases management for maize, cowpea, sweet potato, and vegetables production systems. This bundle helped farmers build resilience through effective management of climate-driven crop pests and diseases while promoting one-health outcomes.